Meal Fatty Acids Have Differential Effects on Postprandial Blood Pressure and Biomarkers of Endothelial Function but Not Vascular Reactivity in Postmenopausal Women in the Randomized Controlled Dietary Intervention and VAScular function (DIVAS)-2 Study. Issue 3 (12th March 2018) - Rathnayake, Kumari M; Weech, Michelle; Jackson, Kim G; Lovegrove, Julie A
Abstract: Background: Elevated postprandial triacylglycerol concentrations, impaired vascular function, and hypertension are important independent cardiovascular disease (CVD) risk factors in women. However, the effects of meal fat composition on postprandial lipemia and vascular function in postmenopausal women are unknown. Objective: This study investigated the impact of sequential meals rich in saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), or n–6 (ω-6) polyunsaturated fatty acids (PUFAs) on postprandial flow-mediated dilatation (FMD; primary outcome measure), vascular function, and associated CVD risk biomarkers (secondary outcomes) in postmenopausal women. Methods: A double-blind, randomized, crossover, postprandial study was conducted in 32 postmenopausal women [mean ± SEM ages: 58 ± 1 y; mean ± SEM body mass index (in kg/m 2 ): 25.9 ± 0.7]. After fasting overnight, participants consumed high-fat meals at breakfast (0 min; 50 g fat, containing 33–36 g SFAs, MUFAs, or n–6 PUFAs) and lunch (330 min; 30 g fat, containing 19–20 g SFAs, MUFAs, or n–6 PUFAs), on separate occasions. Blood samples were collected before breakfast and regularly after the meals for 480 min, with specific time points selected for measuring vascular function and blood pressure. Results: Postprandial FMD, laser Doppler imaging, and digital volume pulse responses were not different after consuming the test fats. The incremental area under the curve (iAUC) for diastolic blood pressure was lower after the MUFA-rich meals than after the SFA-rich meals (mean ± SEM: −2.3 ± 0.3 compared with −1.5 ± 0.3 mm Hg × 450 min × 10 3 ; P = 0.009), with a similar trend for systolic blood pressure ( P = 0.012). This corresponded to a lower iAUC for the plasma nitrite response after the SFA-rich meals than after the MUFA-rich meals (−1.23 ± 0.7 compared with -0.17 ± 0.4 μmol/L × 420 min P = 0.010). The soluble intercellular adhesion molecule 1 (sICAM-1) time-course profile, AUC, and iAUC were lower after the n–6 PUFA-rich meals than after the SFA- and MUFA-rich meals ( P ≤ 0.001). Lipids, glucose, and markers of insulin sensitivity did not differ between the test fats. Conclusion: Our study showed a differential impact of meal fat composition on blood pressure, plasma nitrite, and sICAM-1, but no effect on postprandial FMD or lipemia in postmenopausal women. This trial was registered at www.clinicaltrials.gov as NCT02144454.